2011
DOI: 10.1007/s11547-011-0692-7
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sarcoma: CT imaging of a rare primary malignant tumour of the thorax

Abstract: Although PSSL is a rare tumour, a pulmonary mass of inhomogeneous density, associated with pleural effusion but without lymphadenopathy, detected in an asymptomatic or poorly symptomatic patient, should lead to PSSL being considered in the differential diagnosis, provided that metastases from the more common synovial sarcomas of the musculoskeletal system have been excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
0
21
1
Order By: Relevance
“…It is often difficult to determine the exact site of the primary tumor in terms of whether it is pleural or parenchymal, and therefore, it is often referred to as PPSS. PPSS usually affects people in the 4th or 5th decade of life 1 , 4 , 5 with a reported age ranged between 9 and 77 years [5] . The literature either describes no specific sex predilection 2 , 5 , 6 or a slight male predominance 1 , 3 , 7 .…”
Section: Discussionmentioning
confidence: 99%
“…It is often difficult to determine the exact site of the primary tumor in terms of whether it is pleural or parenchymal, and therefore, it is often referred to as PPSS. PPSS usually affects people in the 4th or 5th decade of life 1 , 4 , 5 with a reported age ranged between 9 and 77 years [5] . The literature either describes no specific sex predilection 2 , 5 , 6 or a slight male predominance 1 , 3 , 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that PET is useful in the follow-up of synovial sarcoma 1,23. PET/CT has also been used as a diagnostic tool for synovial sarcoma, as well as lymphoma 20,28,29. Charest et al .…”
Section: Discussionmentioning
confidence: 99%
“…The local recurrence rate of synovial sarcoma is 8–60%. Tumours usually recur within 2 years of the initial therapy 20. The diagnostic workup for recurrence or metastasis of synovial sarcoma involves conventional imaging, including computed tomography (CT) and magnetic resonance imaging (MRI) 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polverosi et al 5 have recently reported three cases with pulmonary synovial sarcoma presenting with big masses with inhomogeneous density in lungs, pleural effusion and absence of significant mediastinal lymph node enlargement. Primary synovial sarcoma of thorax is a rare tumor and can originate from lung parenchyma, pleura, mediastinum or chest wall.…”
Section: Discussionmentioning
confidence: 99%